TANGGUNGJAWAB ORANG TUA TERHADAP HAK HADHANAH DAN NAFKAH ANAK PASCA PERCERAIAN: Perspektif Hukum Islam dan Putusan Pengadilan Agama - Ramlah Ramlah (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2021)
The study aims to describe islamic law's review of parents' obligations to provide custody and livelihood of children post-divorce. This research uses literature study methods. The results showed that if there is a child divorce that has not been mumayyiz then custody of the child is handed over to the female side, and if it is mumayyiz then the custody of the child can follow the female side or follow the male side. While the child's livelihood remains the responsibility of the male side. All divorce rulings in the Jambi Religious Court, deciding the child's livelihood is charged to the male side. There is a similarity of concepts between the concept of Fiqh and the basis of the judge's consideration in deciding the case of the child's income and the right of the child, because the judge in deciding the case refers to the book of Fiqh and the law of family law.